Questioning the compatibility of the infill architecture in historic environment, case study: walled city of Nicosia - Soosani, Leila (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Historic environments are the mirror of cities‟ social, economic, cultural, physical and architectural history. Historic environments start to have changes according to the change in lifestyle, socio-economic standards and technology; therefore, new buildings in historic environment are one aspect of these changes. These new buildings sometimes may constructed in line with the characteristics of the context but sometimes they are constructed without respecting the visual and spatial characters of the context. Therefore, there are some important issues such as the relationship between the new buildings and the existing setting and the quality of them to achieve compatible/contextual design in historic setting and to protect from its identity and values. Walled City of Nicosia in Northern Cyprus has been through the socio-economic devaluation and physical deterioration decline that caused to decay of the architectural quality and loss of population of the historic center. Nevertheless, there are some newly constructed infill projects. Consequently, the aim of this study is to assess the compatibility of the new building in historic context and discuss about their design approaches. Based on the aim this study will have four chapters. Initially, introduction of the study will be given in the first chapter. Then in second chapter, definition of historic environment from different resources, importance and values of historic areas and its visual and spatial characteristics of will be explained. Thus, the criteria for compatible design and new building design approaches will be presented. Also some cases from different European contexts will be analyzed to test these criteria and design approaches. According to the information that gathered from Antiquities Department there are only four infill buildings which are constructed during the last 10 years in Walled City of Nicosia and they will be analyzed. Regarding to the design criteria such as massing, scale, setback, orientation, proportion, rhythm, material, color, sitting and height and accordingly their design approaches and compatibility will be achieved. The methodology of this research includes qualitative research that is based on analysis, literature survey and field studies. Literature survey, about the subject of the study involves: historic environments, conservation, and sense of place, visual and spatial characters. Filed study will be done on the newly constructed architecture in Nicosia. It will consist of observation and photographs and analyzing them according to the mentioned criteria. Based on analysis that conducted in Walled City of Nicosia, out of four new buildings, three of them have compatible/contextual design approaches. However, one of the buildings has free design approach which means designer did not consider visual and spatial characters of the context. Keywords: Historic Environment, Infill Building, Contextual Design, Walled City of Nicosia. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Tarihi çevreler, geçmişte yaşamış farklı kültürlerin soyal, ekonomik ve kültürel izlerini taşırlar. Değişen yaşam koşulları, sosyo-ekonomik koşullar ve teknoloji nedeni ile tarihi çevreler değişmeye başlamıtır. Bu alanlardaki yeni yapılaşmalar da bu değişimin bir parçasıdırlar. Bu uygulamalar bazen nitelikli ve bilinçli, bazen de bulundukları çevreye saygı göstermeyen, görsel açıdan bu çevrelere yakışmayan tasarımlar olmaktan ileriye gidememiştir. Bundan dolayı, yeni binaların kalitesi ve bağlama uygun tasarımları bu alanların kimliğini ve mevcut değerlerinin korunması için önem taşımaktadır. Bu çalışmada örnek çalışma alanı olarak seçilen Lefkoşa Suriçi bölgesi, süregelen fizisel eskime, sosyal ve ekomik çöküntü ve buna bağlı mimari ve fiziksel çevresi eskimesi ve nüfus kaybi gibi problemlerle karşı karşıyadır. Bununla birlikte, bu alanda yeni yapılaşmalar da bulunmaktadır. Bu bağlamda, bu çalışmanın amacı tarihi çevredeki yeni tasarımların ve bu tasarımlar yapılırken uygulanan yötemleri irdelemektir. Bu amaca bağlı olarak, çalışma dört bölümden oluşmaktadır. İlk bölümde giriş kısmı verilirken, ikinci bölüm tezin kavramsal ve kuramsal kısmını oluşturmaktadır. Bu bölüm içerisinde tarihi çevre kavramı üzerinde durulmuş ve tarihi çevrenin mimari değerlerinin saptanması, görsel ve mekansal özelliklerin önemi üzerinde durulmuştur. Bunun yanında; “infill” kavramı, yeni yapılaşmalarla ilgili uluslararası tüzüklerde bulunan prensipler; yeni binalardaki çeşitli tasarım yaklaşımları ve bu tasarımların irdelenmesine temel oluşturacak kriterler ele alınmıştır. Belirlenen bu kriterler çerçevesinde farklı Avrupa kentlerinde uygulanmış yeni bina tasarımları incelenmiştir. Tezin dördüncü bölümünde çalışma alanı olarak seçilen Lefkoşa suriçinde son 10 yılda yapılmış yeni yapılar incelenmiştir. Kuramsal çerçeveden elde edilen kütle, ölçek, geriye çekilme, yönlenme, oran, ritim, malzeme, renk, pozisyon/konum ve yükseklik tasarım kriterleri araştırılmış ve bu binaların tarihi çevreye uyumu ile tasarım yaklaşımları ortaya konmuştur. Tezin dördüncü bölümünde ise elde edilen sonuçlar ve görüşler verilmiştir. Çalışmanın amacına bağlı olarak, konu ile ilgili literature taraması ve saha çalışması yapılmıştır. Yapılan analizler sonunda, Lefkoşa suriçi bölgesinde son 10 yılda yapılan dört adet yeni bina tespit edilmiş ve bu binaların üç tanesi bulundukları çevre ile uyumlu tasarımlara sahip oldukları saptanmıştır. Diğer bina ise çevrenin göresel ve mekansal özellikleri dikkate alınmadan yapıldığından, bu çevreyi hiçe sayan özgür bir tasarıma sahip olduğu saptanmıştır. Anahtar Kelimeler: Tarihi Çevre, Mekansal Özellikler, Venedik Tüzüğü, Yeni Bina, Bağlama Uyumlu Tasarımlar, Lefkoşa Suriçi.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Assoc. Prof. Dr. Beser Oktay Vehbi.
Keywords: Architecture; Urban Design; Historic Buildings - Sustainability - Nicosia (Cyprus, North); Historic buildings - Conservation - Walled City - Nicosia (Cyprus, North)